ASSOCIATION BETWEEN RISK OF FALL AND RELATED FACTORS IN SARCOPENIA PATIENTS - Nguyen, Thi Hoai Thu; Vu, Thi Thanh Huyen; Tran, Viet Luc; Nguyen, Ngoc Tam; Vu, Thi Thanh Huyen; Nguyen, Trung Anh (Tạp chí Sinh lý học Việt Nam, 2023)
Objectives: This study aims to evaluate related factors affecting the risk of fall in older sarcopenic patients. Methods: A cross-sectional study was conducted in 294 participants aged ≥ 60 years old at National Geriatric Hospital in Hanoi, Vietnam, from July to October 2022. Sarcopenia was defined by the criteria proposed by Asian Working Group for Sarcopenia (AWGS 2019). Risk of fall was assessed through a 21-item index. The T-test and Chi-square test were used to compare groups. The relationship between sarcopenia and risk of fall was estimated by deriving odds ratios from multiple logistic regression models. Results: The mean age of participants was 75.68 ± 8.20 years, and 78.2% were female. In multivariate logistic regression, age (adjusted OR = 2.907, 95% CI: 1.777–4.754), marital status (adjusted OR = 2.352, 95% CI: 1.390–3.979), diabetes (adjusted OR = 1.994, 95% CI: 1.225–3.246), heart failure (adjusted OR = 1.947, 95% CI: 1.086–3.493), depression (adjusted OR = 2.298, 95% CI: 1.005–5.253), hypertension (adjusted OR = 1.885, 95% CI: 1.166–3.046), ADL (adjusted OR = 4.724, 95% CI: 2.867–7.783), IADL (adjusted OR = 8.403, 95% CI: 4.689–15.061), and sleep quality (adjusted OR = 3.027, 95% CI: 1.837–4.987) were significantly associated with a high risk of fall in sarcopenic patients defined by the AWGS 2019 criteria. Conclusion: Patients with sarcopenia have a high prevalence of falls and a high risk of falling. Fall risk assessment and implementation of fall prevention strategies should be carried out in everyday clinical practice.